Residual power series algorithm for fractional cancer tumor models - Korpinar, Zeliha; İnç, Mustafa; Hincal, Evren; Baleanu, Dumitru (Elsevier, 2020)
In this paper, the new series solutions of some fractional cancer tumor models are investigated by using residual power series method (RPSM). The RPSM is explained with Maclaurin expansion for the solution. One of the advantages of this method is quick and easy calculation to find series solutions by using mathematica software package. Graphical presentations for series solutions are given to explanation of the method. The obtained outcomes explain that process is applicable and reliable method to obtain numerical solutions of fractional equations. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Residual power series method; Series solution; Caputo fractional derivative; Fractional cancer tumor models